(untitled) (Baghdad Science Journal, 2025)
Three N-(hydroxylphenyl) dimethylmaleimides were directly prepared in good yields (81-86)% from the reaction of dimethylmaleic anhydride with amino phenols. The prepared imides were esterified to the corresponding benzoates, methacrylates and cinnamates via their reaction with different acid chlorides in the presence of triethylamine. The prepared esters were tested as plasticizers for PVC via preparing of thirty six samples of PVC with the prepared esters in certain weight ratio followed by recording their softening points. Comparison the results with the universal plasticizers for PVC (DOP) and (DBP) indicated that the prepared esters in general have high plasticizing efficiency.